Antimicrobial Resistance in Enterococcus spp. Isolates from Red Foxes (Vulpes vulpes) in Latvia - Margarita Terentjeva; Juris Ķibilds; Jeļena Avsejenko; Aivars Cīrulis; Linda Labecka; Aivars Bērziņš (MDPI AG, 2024)
Antimicrobial resistance (AMR) is an emerging public health threat and is one of the One Health priorities for humans, animals, and environmental health. Red foxes (Vulpes vulpes) are a widespread predator species with great ecological significance, and they may serve as a sentinel of antimicrobial resistance in the general environment. The present study was carried out to detect antimicrobial resistance, antimicrobial resistance genes, and genetic diversity in faecal isolates of red foxes (Vulpes vulpes). In total, 34 Enterococcus isolates, including E. faecium (n = 17), E. faecalis (n = 12), E. durans (n = 3), and E. hirae (n = 2), were isolated. Antimicrobial resistance to 12 antimicrobial agents was detected with EUVENC panels using the minimum inhibitory concentration (MIC). The presence of antimicrobial resistance genes (ARGs) was determined using whole-genome sequencing (WGS). Resistance to tetracycline (6/34), erythromycin (3/34), ciprofloxacin (2/34), tigecycline (2/34), and daptomycin (2/34) was identified in 44% (15/34) of Enterococcus isolates, while all the isolates were found to be susceptible to ampicillin, chloramphenicol, gentamicin, linezolid, teicoplanin, and vancomycin. No multi-resistant Enterococcus spp. were detected. A total of 12 ARGs were identified in Enterococcus spp., with the presence of at least 1 ARG in every isolate. The identified ARGs encoded resistance to aminoglycosides (aac(6')-I, ant(6)-Ia, aac(6')-Iih and spw), tetracyclines (tet(M), tet(L) and tet(S)), and macrolide-lincosamide-streptogramin AB (lnu(B,G), lsa(A,E), and msr(C)), and their presence was associated with phenotypical resistance. Core genome multilocus sequence typing (cgMLST) revealed the high diversity of E. faecalis and E. faecium isolates, even within the same geographical area. The distribution of resistant Enterococcus spp. in wild foxes in Latvia highlights the importance of a One Health approach in tackling AMR.